Magnetic field regulated, controlled hyperthermia with Li x Fe 3-x O 4 (0.06 ≤ x ≤ 0.3) nanoparticles - Srivastava M.; Alla S.K.; Meena S.S.; Gupta N.; Mandal R.K.; Prasad N.K. (My University, 2025)
The single phase Li x Fe 3-x O 4 (0.06 ≤ x ≤ 0.3) nanoparticles were synthesized using microwave refluxing technique and found to be spherical with the size in the range of ∼ 3–22 nm. The structure and the size were confirmed by X-ray diffraction patterns and transmission electron microscopy. X-ray photoelectron spectroscopy data of Li 0.3 Fe 2.7 O 4 sample indicate the oxidation states for Li-ions (+1) and Fe-ions (+2 and + 3). The sample Li 0.06 Fe 2.94 O 4 had superior magnetization value (∼54.1 Am 2 /kg) and it diminished with increasing Li content. The low coercivity values and the presence of a doublet in Mössbauer spectra advise the presence of both ferrimagnetic and superparamagnetic component. The ferrofluids of these samples show magnetic field dependent stabilization of temperature near 42 °C at the time of magnetic hyperthermia experiments. The specific absorption rate value (up to 100 W/g) found to be comparable with the literature values. © 2019 Elsevier Ltd and Techna Group S.r.l.